A second view on the possible enhancement of distillation efficiency with nanofluids. (October 2017) - Eggers, Jan Rudolf; Kabelac, Stephan
Abstract: A considerable increase in thermal separation by the use of radiation induced evaporation of binary base fluids using nanofluids has been reported. It was shown for the water-ethanol system, that the vapor phase composition was enhanced about 20 wt% of ethanol above the thermodynamic equilibrium value. Even the azeotropic point seemed to disappear. This paper aims to reproduce the reported results and it tries to analyze possible mechanisms explaining these findings that appear anomalously at first sight.